Nghiên cứu đề xuất phương án điều tra sử dụng thời gian phục vụ tính toán nhân lực nghiên cứu khoa học và phát triển công nghệ theo FTE - Tào, Hương Lan (Cục Thông tin khoa học và công nghệ quốc gia, 2023)
In R&D personnel statistics, full-time equivalent employee calculator (FTE) is key to adequately measuring the actual volume of R&D personnel, maintaining the international comparison. The article analyses research on identifying the conversion ratio to measure the FTE R&D personnel from the R&D personnel per capita database, including: FTE definition, Time-use survey methodology in R&D personnel statistics; R&D researcher time-use survey methodology option